Evaluating the Economic Feasibility of Hydroponics in Urban Agriculture at Kathmandu, Nepal - Baniya, Usha; Khaniya, Sachin; Karki, Rojan (Nepalese Journal of Agricultural Sciences, 2025)
This review paper explores hydroponics as a progressive method of urban agriculture, addressing challenges of confined land availability, food security, and environmental worries resulting from urbanization. Hydroponics, a soilless agricultural technique, emerges as a sustainable response to the urban challenges of limited arable land and water scarcity. Overall, this review synthesizes the study's insights into setup costs, operational challenges, and profitability, aligning them with global trends and local constraints. Recommendations for strategic interventions, including subsidies, training, and urban planning integration, highlight pathways to foster the adoption of hydroponic farming in urban contexts.